Confinement of Magnetic Nanoparticles Inside Multisegmented Nanotubes by Means of Magnetic Field Gradients - Altbir-Drullinsky, D; Escrig-Murua, J; Allende-Prieto, S (2012)
The possibility of confining magnetic nanoparticles inside multisegmented nanotubes by using strong field gradients is considered by means of Monte Carlo simulations. The problem is reduced to the random walk performed by the nanoparticle on the energy landscape produced by the tube s magnetic field. The role of tube material, number of segments, and spacer thickness in the amount of time spent by the particle inside the tube is examined, concluding that it is possible to control the encapsulation time by using different architectures. © 2012 American Institute of Physics.